Vision of multidisciplinary team on the role of physiotherapy in a public home care program - Melher Pereira, Bibiana; Gessinger, Cristiane Fernanda (O Mundo da Saúde, 2014)
Public home care seeks to ensure integral care to individuals by promoting continuity of care and the expansion of their autonomy. This assistance can be provided as part of health promotion, prevention and treatment of illness and rehabilitation. Within this model of care named Home Care Program of the Bedridden (PADA), which involves multidisciplinary health care. In this context, the aim of this work is to characterize the population served by home physical therapy as well as the profile of caregivers, and assess, in view of the multidisciplinary team, the role of physiotherapy in PADA. A quantitative and transversal study was conducted by collecting data from patients and caregivers in evolution files. The exploratory and descriptive qualitative part of the study took place by means of interviews with the seven components of PADA professionals, which were asked about the contribution of physiotherapy performance for the individuals served. The population served is predominantly old people and have chronic diseases, and are cared mostly by family caregivers, most of them old. After analysis, the objectives found for home physical therapy were: functionality, improved posture, vestibular rehabilitation, respiratory focus, prevention, guidelines and adhesion to family care. The contribution of physical therapy was divided into the following categories: improved quality of life, emotional aspects, respiratory focus, improved positioning in bed, decreased muscle pain, motor function, prevention and ergonomic issues. For the multidisciplinary team, physical therapy the home care program is beneficial for maintaining or acquiring functionality of patients to avoid episodes of hospitalization for those having respiratory ailments, in addition to allowing aid to caregivers by means of the guidelines. One can infer that the role of physiotherapy in PADA is vital for the maintenance of functional capacity in respiratory and motor aspects of users, and it also helps caregivers’ performance in order to avoid an overload of home care. However, the role of physiotherapy must focus on rehabilitation and comprehensive health care, and integral perspectives are still incipient as regards primary health care